NANOCELLULOSE OBTAINED MECHANICALLY BY DIFFERENT COLLOID GRINDING INTENSITIES - Stygar Lopes, Marina; Potulski, Daniele Cristina; Cássia Viana, Lívia; Elita Carneiro, Mayara; Inês Bolzon de Muniz, Graciela; Sulato de Andrade, Alan (Floresta, 2019)
Recent advances in nanocellulose technology have enabled production of materials for various applications with attractive properties. The aim of this work was to analyze the nanofibrillated cellulose of Eucalyptus sp. obtained by different grinding intensities. Delignified Eucalyptus sp. kraftpulp was used to obtain the nanofibrillated cellulose in the mechanical grinding process, with 2, 10 and 20 passes. Images were captured by scanning and transmission electron microscopy to observe cellulose structures. For each mechanical treatment, three films were produced, which were used to evaluate the crystallinity index. Viscosity measurement evaluated the influence of mechanical treatment on nanofibrillated cellulose. Microscopic analysis showed that the mechanical process promoted fiber defibrillation, resulting in the exposure of microfibrils in all treatments evaluated. Differences were not verified in the conformation and dimensions of the structures for the different numbers of passes, and the nanofibrils presented average diameter of approximately 30 nm. The mechanical process to obtain the nanofibrillated cellulose reduced of the crystallinity index and the viscosity of the nanofibrillated cellulose compared to cellulose before processing. The average particle size declined with rising number of grinder passes.